Web-Based Online Learning System MVC Method - Salmiati; Mardi Turnip (Institute of Computer Science (IOCS), 2021)
Along with the development of information technology, internet-based technology is also developing which is considered one of the tools for fast delivery of information. Information technology really helps the learning process in schools, one of which is the impact of its development. Information technology is a pattern of change in education. Education uses information technology to assist in the distance learning process electronically by using a computer as a tool. This assistance is known as e-Learning. With e-Learning, students can learn independently without having to constantly expect teaching materials from the teacher. E Learning also allows students to study only in the classroom but also outside the classroom or anywhere as long as they are connected to the internet. All student activities such as access to grades, schedules, and others can be accessed in this e-Learning application.